Developmental Differences in Sleep's Role for Implicit Off-line Learning: Comparing Children with Adults - Fischer, Stefan; Wilhelm, Ines; Born, Jan (Journal of cognitive neuroscience, 2007)
Sleep crucially contributes to the off-line consolidation of memories. Although this view was confirmed in numerous studies in adults, it is not known whether it can be generalized to sleep during development. Here, we examined effects of sleep on implicit memory formation considered of particular relevance in children, because brain structures underlying implicit learning develop earlier in ontogeny than structures supporting explicit learning. Subjects were 7- to 11-year-old children ( = 14) and 20- to 30-year-old adults ( = 12) tested on a serial reaction time task before (learning) and after (retest) equal length retention periods of overnight sleep and daytime wakefulness. At learning, after eight training blocks, all subjects had acquired implicit knowledge of the probabilistic rules underlying the sequential stimulus materials, as indicated by a substantial difference in response time to grammatical versus nongrammatical trials in two test blocks that followed the training blocks. At learning, this response time difference was greater in children (48.49 ± 6.08 msec) than adults (28.02 ± 3.65 msec, < .01), but did not differ between sleep and wake retention conditions in either age group. Consistent with previous studies, retesting in the adults revealed that the reaction time differences between grammatical and nongrammatical trials increased by 9.78 ± 4.82 msec after sleep, but decreased by −12.76 ± 5.49 msec after the wake retention period ( < .01). Contrary to this finding in adults, sleep in children did not lead to an increase, but to a decrease in the reaction time difference averaging −26.68 ± 12.25 msec ( < .05), whereas across the wake retention interval the reaction time difference remained nearly unchanged. The sleep-dependent deterioration in measures of implicit sequence knowledge in children was in striking contrast to the gain of such knowledge in the adults during sleep ( < .01). Our findings indicate that the functional role of sleep in implicit memory consolidation depends on age. We speculate that the overnight decrease of implicit knowledge in children reflects a preferential effect of sleep toward the enhancement of explicit aspects of task performance that interferes with implicit performance gains.